Development of accounting learning media based on wetland environment for high school students in South Kalimantan - Noor Eka Chandra; Maulana Rizky; Lufna Bariroh; Abdul Irvan Arista (International Ecsis Association, 2023)
This study aims to develop a wetland-based accounting learning media for high school students in South Kalimantan. This study measures the feasibility of learning media developed with the validation of media experts and practitioners. The form of research and development uses model ADDIE which consists of five stages, namely analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The instruments used are validation sheets and student response questionnaires. The method used in data collection is interviews for initial research data and validation. The research step of the learning media development process starts from stage (1) Analysis, The analysis stage is the stage of analyzing the need for the development of new learning models/methods and analyzing the feasibility and requirements of developing new learning models/methods. The analysis phase includes curriculum analysis and student characteristics analysis. (2) Design, At this stage, the design of learning media development is carried out in the form of an initial design that is in accordance with the analysis that has been done previously. (3) Development, the development stage is the stage of product realization that is ready to be implemented. (4) Implementation, at this stage, the implementation is carried out in a limited manner at the designated school as the research site. (5) Evaluation, at this stage, researchers make revisions to the developed media based on criticism and suggestions obtained from the response questionnaire or field notes.